QUALITY OF AN E-LEARNING VIRTUAL COURSE IN HEALTH SCIENCES (Revista Electrónica Calidad en la Educación Superior, 2017)
A descriptive study was conducted in order to evaluate the quality of a virtual course on teacher training, using the Evaluation Model of the Virtual Continuous Training Courses of the Latin American Institute for Quality in Distance Education (CALED, in Spanish). By applying a checklist and four questionnaires, there were analyzed 72 indicators for the following areas: Technological quality, training, instructional design and services and support. The results indicate a partial accomplishment of the quality standards. The areas of greatest fulfillment in descending order were training, instructional design and services and support. In the area of technological quality most of the requirements were met, but in many cases, no required records were found as evidence at the time of the assessment.